Comparison of Educational and Occupational Aspirations of Rural Youth from Farming Families of Kerala and Rajasthan - Hari, R.; Chander, Mahesh; Sharma, N. K. (Indian Journal of Extension Education, 2013)
Aspirations act as key motivator in success of any individual. Lower aspirations are often ascribed as one of the reasons for  lower achievement of any individual including the rural youth. Two hundred youth respondents from farming families of  Kerala and Rajasthan were interviewed to analyze their educational and occupational aspirations and the effect of socio cultural and economic factors on aspirations. The results revealed that only a small fraction of youth were interested in  agriculture and allied industries in both of these states. The study found that socio--cultural factors influenced the  educational and occupational aspirations of the respondents. A significant variation between the aspirations of  respondents of both states was observed in the study. Certain social factors viz teachers, relatives & neighbours, media and  social acceptance had more influence on respondents in one state than other, indicating the importance of socio-cultural  factors prevailing in the society. The study has also highlighted that aspiration is one of the important element influencing  the youth educational and occupational preference and hence, should be analyzed in harmony with other elements to  enable more rational and scientific policies in this context.
Keywords: Aspirations; educational; occupational; rural youth; farming; Kerala; Rajasthan